POTENSI BUDAYA MINUM KOPI (NGOPI) DALAM MEMBANGUN KEMBALI KOEKSISTENSI MASYARAKAT ACEH PASKA KONFLIK - Danil Akbar Taqwadin; Ahmad Nidzamuddin Sulaiman; Saiful Akmal; Indra Fauzan (Universitas Islam Negeri Ar-Raniry, 2019)
The widespread and prolonged violent conflict in Aceh has passed down negative legacy within a vulnerable communities. One of the most-exposed the social capital elements is the mutual trust or the excessive manifestation of hate. Although suspicion often provides a sense of security in violent conflict, yet when peace is present, the inherent feeling of distrust can disrupt the construction of community coexistence towards reconciliation. However, with the development of a fairly massive coffee culture, promising opportunities to construct coexistence in post-conflict societies in Aceh emerged. Therefore, this study uses a narrative approach in describing the potentials of coffee culture in constructing the coexistence of post-conflict communities in Aceh.